‘Emergency chemotherapy’ for bleeding cervical cancer: case series - Shafiee, MN; NorAzlin, MI; Lim, PS; Trika, I; Arifuddin, D; Hatta, D (Department of Surgery, UKM Medical Centre, 2012)
Fulminant haemorrhage in cervical cancer leads to severe anaemia and haemodynamic instability. Palliative management includes vaginal packing as temporary measure, radiotherapy and other invasive surgical procedures. High dose emergency chemotherapy is not commonly implemented particularly when complicated with anaemia and renal impairment. We discuss three case series on the usefulness of high dose chemotherapy to combat bleeding from cervical cancer as an emergency treatment. The first case was clinically staged as operable 2A disease with severe anaemia due to bleeding from the tumour mass. The haemoglobin was corrected by blood transfusion while the bleeding was being arrested by high dose chemotherapy. The second case was inoperable with invasion to the bladder mucosa. She had frank haematuria and bleeding from the tumour with severe anaemia. A course of chemotherapy and blood transfusion controlled the bleeding and anaemia was corrected. The third case presented late with obstructive uropathy and anaemia. She required dialysis, blood transfusion and high dose emergency chemotherapy to stop the bleeding before undergoing urinary diversion after an unsuccessful ureteric stenting. High dose chemotherapy consisting cisplatin, vincristine, bleomycin and mitomycin-C has a clinical value in arresting fulminant haemorrhage in cervical cancer.